Investor Reaction To The Implementation Of Sustainability Reporting - Pulungan, Riski Hamdani; Khomsiyah, Khomsiyah (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The purpose of the disclosure of Sustainability Reporting is to solve social and environmental issues and may have an impact on achieving sustainable development in the face of social responsibility issues. In addition, Sustainability Reporting Disclosures can be used to achieve company goals. This study aims to analyze the implementation of Sustainability Reporting and whether it affects investor reactions in considering investment decisions. Sustainability Reporting disclosure in this study was tested as an independent variable with control variables EPS, PBV, and Dividends. An increase or decrease in stock prices indicates that investors react to the information disclosed, in this study, stock prices were tested as the dependent variable. The total research sample is 30 companies listed on the Indonesia Stock Exchange, with the category of companies getting an assessment rating from the National Center for Sustainability Reporting (NCSR). The results of hypothesis testing show that Sustainability Reporting disclosures have a significant effect on stock prices, so it can be concluded that Sustainability Reporting disclosures can provide a reaction to investor decisions. Control variables EPS, PBV, and Dividend Policy significantly affect stock prices.